FORMULASI MINUMAN SUPLEMEN DAUN TORBANGUN (Coleus amboinicus Lour.) UNTUK WANITA YANG MENDERITA PMS (PREMENSTRUAL SYNDROME) - Pramadya Alfitra; Budi Setiawan; M. Rizal Damanik (Food and Nutrition Society of Indonesia, 2010)
Torbangun (Coleus amboinicus Lour) is one of Labiatae family containing a lot of micronutrients and active components. The plant is used as traditional medicine for relieving premenstrual syndromes (PMS). Based on the results of previous studies, a capsule containing 750 mg of dried Torbangun leaves can relieve PMS as well as commercial herbal, and better than placebo. Capsule supplement form seems less acceptable because it tastes like taking a drug. Therefore, it requires development for Torbangun supplement product in other forms, and one of them is a supplement drink. The study is aimed to formulate a supplement drink from Torbangun leaves as the basic ingredients. Supplement drink formulation is made in trial and error by combining extract of torbangun leaves, sucrose, and lemon, obtaining three formulas: DT1 contains 10 g extract of torbangun leaves and 16 g sucrose, DT2 contains 10 g extract of torbangun leaves, 2 g lemon, 22 g sucrose, and DT3 contains 10 g extract of torbangun leaves, 4 g lemon, and 28 g sucrose. These formulas are then tested by organoleptic, physical, and chemical. The results show that the formula DT3 has the highest average score. Blanching treatment improves organoleptic properties of supplement drinks. Mean scores in color, aroma, and taste of the blanched supplement drink are different (p<0.05) from non-blanched supplement drink.